2018
DOI: 10.24095/hpcdp.38.11.02
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with sleep duration across life stages: results from the Canadian Health Measures Survey

Abstract: Introduction Sleep is essential for both physical and mental well-being. This study investigated sociodemographic, lifestyle/behavioural, environmental, psychosocial and health factors associated with sleep duration among Canadians at different life stages. Methods We analyzed nationally representative data from 12 174 Canadians aged 3–79 years in the Canadian Health Measures Survey (2009–2013). Respondents were grouped into five life stages by age in years: preschool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 55 publications
(103 reference statements)
2
40
0
2
Order By: Relevance
“…Similar to our findings in adults with hypertension, many previous studies in the general population have found no association between habitual sleep duration and COPD, heart disease, diabetes [16,47], stroke [16,47], or arthritis [13,16]. However, other studies found that short sleep duration was significantly associated with COPD [13], heart disease [13,14], and arthritis [47], while stroke was associated with long sleep duration [43].…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our findings in adults with hypertension, many previous studies in the general population have found no association between habitual sleep duration and COPD, heart disease, diabetes [16,47], stroke [16,47], or arthritis [13,16]. However, other studies found that short sleep duration was significantly associated with COPD [13], heart disease [13,14], and arthritis [47], while stroke was associated with long sleep duration [43].…”
Section: Discussionsupporting
confidence: 87%
“…Third, only college students were included in the study and the findings may not be generalizable to other age groups as there may be age-related differences in sleep patterns and activity levels. 35 More studies are needed to identify whether or not the observed associations vary by age groups.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Exposure to light at night is suspected to disrupt the diurnal cycling of melatonin 2 and cortisol. 3 Circadian disruption due to shift work may also affect hormones governing appetite and satiety, 4,5 which may affect dietary behavior, 6 and can alter sleep patterns, 7,8 which, in turn, can increase metabolic health risks. 9 Prior studies have found relationships between shift work and indicators of metabolic health including BMI (body mass index) increases 10 and risk of obesity, 11 particularly, abdominal obesity.…”
Section: Introductionmentioning
confidence: 99%